Ensuring accessibility and non-discrimination of people with disabilities : toolkit for using EU Structural and Cohesion Funds (Luxembourg, 2009)
"More than one out of six Europeans in the working age is disabled. Many of them can and want to work, which is why people with disabilities constitute a significant potential for contributing to the economy. It is crucial to follow a preventive approach and appropriately address the needs of people with disabilities in order to allow them to better integrate into the labour market. The guidelines in this book are very useful for project developers and others involved in improving conditions for disabled — as well as for the disabled themselves. This toolkit provides information on how to understand the non-discrimination and accessibility requirements of EU Structural and Cohesion funds. It is designed for managing authorities and project promoters to help them fully ensure the equal treatment of people with disabilities."